2019
DOI: 10.1080/15592294.2019.1633868
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of cannabinoid epigenetics on human development: reflections on Murphy et. al. ‘cannabinoid exposure and altered DNA methylation in rat and human sperm’ epigenetics 2018; 13: 1208-1221.

Abstract: Recent data from the Kollins lab (‘Cannabinoid exposure and altered DNA methylation in rat and human sperm’ Epigenetics 2018; 13: 1208–1221) indicated epigenetic effects of cannabis use on sperm in man parallel those in rats and showed substantial shifts in both hypo- and hyper-DNA methylation with the latter predominating. This provides one likely mechanism for the transgenerational transmission of epigenomic instability with sperm as the vector. It therefore contributes important pathophysiological insights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 189 publications
(215 reference statements)
1
40
0
3
Order By: Relevance
“…The present finding may have arisen either because most of the cardiac defects are higher in high cannabis using areas, or because some of the commoner defects are elevated and these suffice to increase the whole group significantly. This latter was the pattern recently observed in Colorado where atrial septal defect (ASD), ventricular septal defect (VSD) and patent ductus arteriosus (PDA) were all found to be dramatically increased in a temporal pattern closely tracking the increased availability of cannabis in that state ( Colorado: Department of Public Health and the Environment, 2018 ; Reece and Hulse, 2019a, 2019c, 2019d ). Moreover, in the most recent Colorado dataset all cardiovascular anomalies have also risen both against time and against cannabis use ( Colorado: Department of Public Health and the Environment, 2018 ; Reece and Hulse, 2019a, 2020a ).…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…The present finding may have arisen either because most of the cardiac defects are higher in high cannabis using areas, or because some of the commoner defects are elevated and these suffice to increase the whole group significantly. This latter was the pattern recently observed in Colorado where atrial septal defect (ASD), ventricular septal defect (VSD) and patent ductus arteriosus (PDA) were all found to be dramatically increased in a temporal pattern closely tracking the increased availability of cannabis in that state ( Colorado: Department of Public Health and the Environment, 2018 ; Reece and Hulse, 2019a, 2019c, 2019d ). Moreover, in the most recent Colorado dataset all cardiovascular anomalies have also risen both against time and against cannabis use ( Colorado: Department of Public Health and the Environment, 2018 ; Reece and Hulse, 2019a, 2020a ).…”
Section: Discussionsupporting
confidence: 57%
“…Both the American Academy of Pediatrics and the American Heart Association have previously issued a position statement which notes increased rates of ventricular septal defect and Ebstein's anomaly in association with cannabis use ( Jenkins et al, 2007 ). Colorado has recently reported a tripling of the rate of atrial septal defect in that state ( Colorado: Department of Public Health and the Environment, 2018 ; Reece and Hulse, 2019a, 2019d ), and indeed atrial septal defect is noted to be more common in cannabis liberal states across USA based on the National Birth Defects Prevention Network publicly available dataset ( National Birth Defects Prevention Network, 2018 ; Reece and Hulse, 2020d ). A large Hawaiian study of over 300,000 births found that hypoplastic left heart, tetralogy of Fallot, pulmonary valve atresia and or stenosis, ventricular septal defect and atrial septal defect were all increased after prenatal cannabis exposure ( Forrester and Merz, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cannabinoids are known to interact with the immune system at multiple points including CB1 and CB2 receptors, six vanilloid channels, peroxisome proliferator-activated receptors (PPAR's), serotonin, adenosine, histamine, glycine, sphingosine, dopamine and opioid receptors, three class A orphan G-protein coupled receptors (GPCR's), toll-like receptors, Tcells, B-cells, macrophages and regulatory cells, effects on sodium channels and several types of potassium and calcium channels, modulation of GABA signalling and inhibition of cyclooxygenase and lipoxygenase enzymes, bind directly to mitochondria and cannabinoid receptors also form heterodimers with opioid, adenosine, dopamine, GABA and other GPCR's and have myriad and major epigenetic effects [13][14][15][16][17][18][19][20][33][34][35][36][37][38] .…”
Section: Discussionmentioning
confidence: 99%